Porothermoelastic effect on wellbore stability in transversely isotropic medium subjected to local thermal non-equilibrium. (July 2017) - Gao, Jiajia; Deng, Jingen; Lan, Kai; Feng, Yutian; Zhang, Weidong; Wang, Houdong
Abstract: Provided that the hydraulic boundary conditions at the wellbore wall are identified as permeable (PBC) and impermeable (IMPBC) and that the assumption of plane strain holds, the present paper formulates a newly porothermoelastic analytical solution, which is based on the thermodynamic principles, in Laplace space domain for inclined borehole. The adopted linear porothermoelastic model embodies the transient heat transfer process in the presence of local thermal non-equilibrium (LTNE) during the derivation. The solution is available for the cases where the wellbore axis of inclined wellbore is perpendicular to the isotropic plane of the low permeable transversely isotropic porous medium under non-hydrostatic stress field condition. The wellbore problem is decomposed into axisymmetric and deviatoric loading cases. The numerical results of the time-dependent distributions of field variables are obtained by virtue of performing the inversion technique for Laplace transforms. An integrated geomechanical wellbore stability model is proposed, which is not only comprised by the abovementioned new porothermoelastic solution, but also associated with the theoretical derivations of strength criteria to evaluate the rock to shear failure, which include Mogi-Coulomb criterion and single weak plane criterion. When a horizontal borehole is drilled along the direction of in the minimum horizontal in-situ stress, the numerical comparative analyses in the present paper examine the combined influence of material anisotropy and thermal effect, which embody in the LTNE and local thermal equilibrium (LTE) models, on the thermally induced pore pressure, stresses and the shear and tensile failure regions around the wellbore. Highlights: Propose a porothermoelastic solution based on local thermal non-equilibrium. Perform the theoretical derivation of Mogi-Coulomb strength criterion. Reveal the conditions required for initiating the transverse fracturing.